Pharmacometrics‐guided drug development of antihyperhidrosis agents. (18th June 2015) - Mehrotra, Shailly; Schmith, Virginia D.; Dumitrescu, Teodora Pene; Gobburu, Jogarao
Abstract The objective of the present work was to use modeling and simulation to inform trial design of a proof‐of‐concept study for agents used in the treatment of hyperhidrosis. Data were available from 36 subjects who received the vehicle, 2% or 4% topical glycopyrrolate wipes daily for 4 weeks, with response (hyperhidrosis disease severity scale [HDSS] and sweat production [SP]) measured weekly. The HDSS and SP time courses were best described using a longitudinal model with maximum response achieved by 1 week. Glycopyrrolate 4% had a higher HDSS responder rate than 2% (50% vs 33%) and placebo (0%) at week 1. Mean change from baseline (mg/5 min [SD]) in SP at week 1 was ‐90 (220), ‐185 (214), and ‐271 (265) for placebo, 2%, and 4% glycopyrrolate, respectively. Subjects with higher baseline SP had higher sweat reduction from baseline. Virtual clinical trials were simulated and analyzed using conventional (at the end of the study) versus model‐based methods to determine sample size for achieving 80% power to identify a dose–response relationship. Twenty‐seven subjects compared with at least 120 subjects would be needed using model‐based and conventional methods, respectively. Thus, the model‐based method using longitudinal data required fewer subjects than the conventional single‐point method.